2014
DOI: 10.1002/esp.3641
|View full text |Cite
|
Sign up to set email alerts
|

Development of ST:REAM: a reach‐based stream power balance approach for predicting alluvial river channel adjustment

Abstract: River channel sediment dynamics are important in integrated catchment management because changes in channel morphology resulting from sediment transfer have important implications for many river functions. However, application of existing approaches that account for catchment‐scale sediment dynamics has been limited, largely due to the difficulty in obtaining data necessary to support them. It is within this context that this study develops a new, reach‐based, stream power balance approach for predicting river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…One such approach to emerge is the Stream Reach Equilibrium Assessment Method (ST:REAM) of Parker et al [118], where specific stream power is applied as an index of sediment discharge and balances between adjacent reaches indicate predominant sediment transporting behaviour. In ST:REAM, a single reference flow is used in the stream power calculation, corresponding to the Flood Estimation Handbook (FEH) index flood (with return period of two years) based on the network of flow gauging stations in England and Wales [119].…”
Section: Stream Energy Approaches In Fluvial Studies: Underpinning Comentioning
confidence: 99%
See 4 more Smart Citations
“…One such approach to emerge is the Stream Reach Equilibrium Assessment Method (ST:REAM) of Parker et al [118], where specific stream power is applied as an index of sediment discharge and balances between adjacent reaches indicate predominant sediment transporting behaviour. In ST:REAM, a single reference flow is used in the stream power calculation, corresponding to the Flood Estimation Handbook (FEH) index flood (with return period of two years) based on the network of flow gauging stations in England and Wales [119].…”
Section: Stream Energy Approaches In Fluvial Studies: Underpinning Comentioning
confidence: 99%
“…While Parker et al [118] reported strong correspondence between ratios of specific stream power and the sequence of erosion-or deposition-dominated reaches in the River Taff, South Wales, UK, four significant issues remain as potential limitations:…”
Section: Stream Energy Approaches In Fluvial Studies: Underpinning Comentioning
confidence: 99%
See 3 more Smart Citations